Bonding of Composite Resin to Alumina and Zirconia Ceramics with Special Emphasis on Surface Conditioning and Use of Coupling Agents - Heikkinen, Timo (Annales Universitatis Turkuensis D 965, 2011)
Dental oxide ceramics have been inspired by their biocompability and mechanical properties which have made durable all-ceramic structures possible. Clinical longevity of the prosthetic structures is dependent on effective bonding with luting cements. As the initial shear bond strength values can be comparable with several materials and procedures, long-term durability is affected by ageing. Aims of the current study were: to measure the shear bond strength of resin composite-to-ceramics and to evaluate the longevity of the bond; to analyze factors affecting the bond, with special emphasis on: the form of silicatization of the ceramic surface; form of silanization; type of resin primer and the effect of the type of the resin composite luting cement; the effect of ageing in water was studied regarding its effect to the endurance of the bond. Ceramic substrates were alumina and yttrium stabilized zirconia. Ceramic conditioning methods included tribochemical silicatization and use of two silane couplings agents. A commercial silane primer was used as a control silane. Various combinations of conditioning methods, primers and resin cements were tested. Bond strengths were measured by shear bond strength method. The longevity of the bond was generally studied by thermocycling the materials in water. Additionally, in one of the studies thermal cycling was compared with long-term water storaging. Results were analysed statistically with ANOVA and Weibull analysis. Tribochemical treatment utilizing air pressure of 150 kPa resulted shear bond strengths of 11.2 MPa to 18.4 MPa and air pressure of 450 kPa 18.2 MPa to 30.5 MPa, respectively. Thermocycling of 8000 cycles or four years water storaging both decreased shear bond strength values to a range of 3.8 MPa to 7.2 MPa whereas initial situation varied from 16.8. Mpa to 23.0 MPa. The silane used in studies had no statistical significance. The use of primers without 10-MDP resulted spontaneous debonding during thermocycling or shear bond strengths below 5 MPa. As conclusion, the results showed superior long-term bonding with primers containing 10-MDP. Silicatization with silanizing showed improved initial shear bond strength values which considerably decreased with ageing in water. Thermal cycling and water storing for up to four years played the major role in reduction of bond strength, which could be due to thermal fatigue of the bonding interface and hydrolytic degradation of the silane coupled interface.

Yhdistelmämuovin sidostaminen alumiinioksidiin ja zirkoniaan painottaen pintakäsittelyä ja sidostusaineiden käyttöä. Hammaslääketieteelliset kokokeraamiset rakenteet ovat tulleet mahdollisiksi oksidikeraamien biologisuuden ja erinomaisten mekaanisten ominaisuuksien ansiosta. Proteettisten rakenteiden kestävyys on riippuvainen onnistuneesta ja tehokkaasta sementoinnista. Vaikka useiden tuotteiden ja menetelmien takaamat sidoslujuudet ovat vertailukelpoisia alkutilanteessa, kestävyyteen ja riittävään sidoslujuuteen vaikuttaa keinotekoinen vanhentaminen. Tämän väitöskirjatyön tavoitteet olivat: mitata yhdistelmämuovin repäisysidoslujuutta keraamiin ja arvioida sen kestävyyttä; edelleen eritellä sidokseen vaikuttavia tekijöitä painottaen: silikoinnin muoto keraamisella pinnalla; silanoinnin muoto; primerin ja resiinin tyyppi; yhdistelmämuovisementin vaikutus; vedessä vanhentamisen vaikutus sidoskestävyyden arvioimiseksi. Keraamiset substraatit olivat alumiinioksidi ja yttriastabiloitu zirkonia. Keraamin esikäsittelytapoihin kuuluivat tribokemiallinen silikointi ja kaksi silaania. Kaupallista tuotetta käytettiin referenssinä. Erilaisia esikäsittelyresiini- ja yhdistelmämuovisementtikombinaatioita tutkittiin. Sidoslujuus testattiin repäisylujuusmenetelmällä. Sidoksen pitkäikäisyys tutkittiin pääasiallisesti termosyklaamalla. Lisäksi yhdessä osatutkimuksessa pitkäaikaisvesisäilytystä verrattiin termosyklaamiseen. Tulokset analysoitiin varianssianalyysillä ja Weibull analyysillä. Tribokemiallinen käsittely käyttäen 150 kPa:n ilmanpainetta tuotti 11,2 – 18,4 MPa:n sidoslujuuden ja vastaavasti 450 kPa:n ilmanpaine 18,2 – 30,5 MPa:n sidoslujuuden.. 8000 kerran termosyklaaminen tai neljän vuoden vesihaudesäilytys laskivat molemmat repäisylujuusarvot 3,8 – 7,2 MPa:iin alkutilanteen vaihdellessa 16,8. – 23,0 MPa.:n välillä. Käytetyllä silaanilla ei ollut tilastollista merkitsevyyttä.. Ilman 10-MDP:tä sisältäviä primereitä tapahtui spontaania koekappaleiden irtoamista tai repäisylujuusarvot jäivät alle 5 MPa:n. Johtopäätöksenä tulokset osoittivat parasta pitkäaikaissidosta primereillä, joissa on 10-MDP:tä. Silikointi ja silanointi osoittivat alkutilanteessa korkeita sidoslujuusarvoja, jotka pienenivät huomattavasti vesihauteessa vanhennettaessa. Termosyklaus ja vesisäilytys neljän vuoden ajan toimivat pääasiallisina tekijöinä sidoslujuuden vähenemisessä, joka voi johtua termisestä väsymisestä sidostumisalueella ja silaanin sidostumisalueen hydrolyyttisestä rappeutumisesta.